Effect of Quinacridone Pigments on Properties and Morphology of Injection Molded Isotactic Polypropylene. (16th March 2017) - Barczewski, Mateusz; Matykiewicz, Danuta; Hoffmann, Bartłomiej
Abstract : Two quinacridone pigments were added (0.01; 0.05; 0.1; 0.5; 1; 2 wt%) to isotactic polypropylene (iPP), and their influence on mechanical and thermomechanical properties were investigated. Complex mechanical and thermomechanical iPP properties analyses, including static tensile test, Dynstat impact resistance measurement, and hardness test, as well as dynamic mechanic thermal analysis (DMTA), were realized in reference to morphological changes of polymeric materials. In order to understand the differences in modification efficiency and changes in polymorphism of polypropylene matrix caused by incorporation of pigments, differential scanning calorimetry (DSC) and wide-angle X-ray scattering (WAXS) experiments were done. Both pigments acted as highly effective nucleating agents that influence morphology and mechanical properties of isotactic polypropylene injection molded samples. Differences between polypropylene samples nucleated by two pigments may be attributed to different heterogeneous nucleation behavior dependent on pigment type. As it was proved by WAXS investigations, the addition of γ -quinacridone (E5B) led to crystallization of polypropylene in hexagonal phase ( β -iPP), while for β -quinacridone (ER 02) modified polypropylene no evidence of iPP β -phase was observed.